The love witch - Biller, Anna ca. 20. Jh (Icon Film Distribution, 2017)
"Elaine, a beautiful young witch, is determined to find a man to love her. In her gothic Victorian apartment she makes spells and potions, and then picks up men and seduces them. However her spells work too well, and she ends up with a string of hapless victims. When she finally meets the man of her dreams, her desperation to be loved will drive her to the brink of insanity and murder. With a visual style that pays tribute to Technicolor thrillers of the 1970s, "The love witch" explores female fantasy and the repercussions of pathological narcissism." [imdb.com]
Original: USA 2016
Bildformat 1.85:1 (16:9)
Special features: behind-the-scenes with writer & director Anna Biller ; extended scenes ; interview with cinematographer M. David Mullen ; deleted & alternate scenes ; Samantha Robinso dance audition ; theatrical trailer
Keywords: Film; DVD-Video